Kreativitas Guru PAI dalam Meningkatkan Kualitas Pembelajaran Pendidikan Agama Islam pada Sekolah Dasar - Sulaiman Ismail; Sulaiman W. (Departement of Mathematics Education, 2023)
This study aims to discover how PAI teachers' creativity in improving the quality of Islamic education at SD Negeri Edit. The method used in this discussion is a field study, to be precise at SD Negeri Sunting. The approach used is qualitative. namely a study aimed at describing and analyzing phenomena, events of social activity, attitudes, beliefs, and perceptions of thought. The results of the discussion show as follows. (1) The creativity of PAI teachers in improving the quality of Islamic education at SD Negeri Sunting is already in the good category. It can be seen that PAI teachers always participate in MGMP (Subject Teacher Deliberations) activities in improving Islamic Religious Education in schools. (2) The supporting factor for the creativity of PAI teachers in improving the quality of learning at SD Negeri Sunting is the support factor from the principal himself. Where the principal always provides the widest possible opportunity and support in developing the quality of PAI teachers. This support is in the form of moral and financial according to the ability of the school. Meanwhile, the inhibiting factor is the lack of financial support provided in realizing teacher creativity in efforts to improve the quality of Islamic Religious Education learning in schools.